Pragmatic Competence and Willingness to Communicate Among L2 Learners of Chinese - Lv, Xiaoxuan; Ren, Wei; Li, Lin (Frontiers in Psychology, 2021)
Research in second language (L2) pragmatics has paid increasing attention to learners’ individual differences, but few studies have examined the relationship between learners’ willingness to communicate (WTC) in L2 and their pragmatic competence. To this end, this study investigates the association between WTC and pragmatic awareness and comprehension of Chinese as a second language(CSL) learners. A total of 80 CSL learners studying abroad in three universities in China participated in this study. Data were collected through a WTC questionnaire, a self-perceived communication competence (SPCC) questionnaire, a pragmatic awareness judgment task, and a multiple-choice test of pragmatic comprehension. Statistical analyses were conducted to analyze the learners’ pragmatic awareness, pragmatic comprehension, their L2 WTC, and their SPCC. The findings indicated that SPCC correlated positively with the learners’ L2 pragmatic comprehension, but not with their L2 pragmatic awareness. No correlation was found between WTC and pragmatic awareness and comprehension. The results suggest that SPCC may contribute to learners’ L2 pragmatic comprehension; some implications for teaching and future research directions are also discussed.